The role of biomass burning agricultural emissions in the Indo-Gangetic Plains on the air quality in New Delhi, India. (1st December 2019) - Bray, Casey D.; Battye, William H.; Aneja, Viney P.
Abstract: Agricultural residue burning in the Indo-Gangetic Plains (IGP) releases large amounts of reactive nitrogen, among other pollutants, into the atmosphere each year. This study focuses on rice paddy residue burning and wheat residue burning during October–November and April–May, respectively, in 2016 and 2017. Emissions of reactive nitrogen species (ammonia (NH3 ), nitrous oxide (N2 O) and oxides of nitrogen (NOx = NO + NO2 )) were estimated for the study period using a suite of satellite products from the Moderate Resolution Imaging Spectroradiometer (MODIS) sensor on the National Aeronautics and Space Administration (NASA) Aqua and Terra satellites. Emissions were compared against ambient concentrations of fine particulate matter (PM2.5 ) in New Delhi, India, to help determine the impact that these agricultural burns have on PM2.5, which is known to have numerous health and environmental impacts associated with prolonged exposure to elevated concentrations. Daily average measured concentrations of PM2.5 in New Delhi range from 22.43 μg m −3 to 718.94 μg m −3 (average 127.15 μg m −3 ± 95.23 μg m −3 ), with the daily average PM2.5 concentration exceeding the national ambient air quality standard of 60 μg m −3 approximately 75% of the time. Concentrations of PM2.5 were found to peak during October–November, which corresponds with rice paddy residue burning in the IGP. In addition to this, statistical regression models were created to predict average daily PM2.5 concentrations in New Delhi, India, based on emissions of NH3 and organic carbon (OC) in the IGP as well as meteorological conditions. The regression model predicted ambient PM2.5 concentrations ranging from 35 to 719 μg m −3 . The average modeled concentrations of PM2.5 in New Delhi, India, were 111 μg m −3 (standard deviation: ± 23 μg m −3 ) during April/May and 207 ± 87 μg m −3 during October/November. Both regression models (for wheat residue burning and for rice paddy residue burning) were comparable to the average observations (normalized mean bias less than 0.1%). Highlights: Wheat residue burning emitted, on average, 71, 940 kg day -1 of NH3, 94, 075 kg day -1 of NOx and 40, 950 kg day -1 of N2 O. Rice paddy residue burning emitted, on average, 416, 511 kg day -1 of NH3, 231, 621 kg day -1 of NOx and 48, 762 kg day -1 of N2 O. Daily PM2.5 in New Delhi peaked during October–November when rice paddy residue burning in the IGP was prevalent. Statistical regressions created predict ambient PM2.5 in New Delhi based on agricultural burning emissions and meteorology.